Exploring Slang Words on Social Media TikTok in 2024 - Jose, Anissa Ikhsan; Nurulaen, Yuyun; Listiani, Toneng (Universitas Muhammadiyah Mataram, 2025)
Slang is rapidly evolving on social media as a form of informal expression, and TikTok has become one of the most dynamic platforms for the spread of slang among the younger generation. This research aims to analyze the types and functions of slang words that develop on the TikTok social media platform in 2024. Using a qualitative approach, this study refers to Allan and Burridge's (2006) classification of slang words, which consists of five categories: fresh and creative, flippant, imitative, acronym, and clipping. Data were obtained from 19 popular TikTok videos, including text in captions, video content, and comments, which featured explicit use of slang expressions. The results show that TikTok users exhibit a high level of linguistic creativity, along with the fast, informal, and multimodal character of digital communication. Of the seven slang functions identified in previous theories, it was found that only three main functions were most dominant, namely: (1) to express impressions, (2) to show closeness or intimacy between users, and (3) to form a relaxed and familiar communication atmosphere. These findings indicate that the use of slang on TikTok not only reflects the dynamics of informal language, but is also an important means of building self-identity and strengthening social relationships among the younger generation. Thus, TikTok can be seen as a digital social space that contributes to the formation and spread of contemporary language innovations.